Komunikasi Keluarga dalam Mendidik Anak di Era Digital - Muhammad Akmal Fathurahim; Oji Kurniadi (Bandung Conference Series: Public Relations, 2022)
Abstrac. The world is facing a growing era, especially in the growth of the world of communication from conventional to digital. Family communication in educating children in this digital era is very much needed, because this digital era can share positive and negative consequences. This research aims to identify the method of talking between parents and children in this digital era, the barriers that exist in the communication of parents and children in the digital era and the position of parents in educating children in the digital era. The method used in this research is a qualitative method with a case study approach. By using interview techniques, field observations, documentation and library research in the search for information. The theory used is the theory of Tabularasa and Theory of Family Communication. The communication approach taken begins with regular stimulation of parents to their children in order to build closeness so that negative things do not happen in the current digital era. The lack of communication between parents and children has a negative impact because in this digital era, the triggers that appear are increasingly varied and information is easily obtained. In the digital era the communication barriers experienced come from gadgets, these barriers make communication less effective. In this digital era, children need parents to act as coaches, coaches and therapists. Parents must always direct their children to stay focused on the path of goodness and parents must be able to play any role according to the child's needs. Abstrak. Dunia hadapi pertumbuhan era, paling utama dalam pertumbuhan dunia komunikasi dari konvensional ke digital. Komunikasi keluarga dalam mendidik anak di masa digital ini jadi sangat dibutuhkan, sebab masa digital ini bisa membagikan akibat positif serta negatif. Riset ini bertujuan buat mengenali metode berbicara orang tua dengan anak di masa digital ini, Hambatan yang terjalin dalam komunikasi orang tua serta anak di masa digital dan Kedudukan Orang tua dalam mendidik anak di masa digital. Peneliti menggunakan metode dalam riset ini merupakan kualitatif dengan pendekatan study kasus. Dengan memakai teknik wawancara, observasi lapangan, dokumentasi serta riset pustaka dalam pencarian informasi. Teori yang digunakan yakni teori Tabularasa serta Teori Komunikasi Keluarga. Pendekatan komunikasi yang dilakukan diawali oleh rangsangan orang tua kepada sang anak secara rutin guna membangun kedekatan dengan agar tidak terjadi hal-hal negatif di era digital saat ini. Kurangnya orang tua berkomunikasi dengan anak memunculkan dampak negatif dikarenakan pada era digital seperti saat ini semakin bervariasi pemicu yang muncul serta mudahnya informasi didapatkan. Di era digital hambatan komunikasi yang dialami berasal dari gadget, hambatan ini menjadikan kurang efektifnya komunikasi yang terjadi. Di era digital seperti saat ini anak membutuhkan orang tua dapat berperan sebagai pelatih, coach serta terapis, Orang tua harus senantiasa mengarahkan sang anak untuk tetap fokus dijalur kebaikan serta orang tua harus bisa berperan apapun sesuai kebutuhan sang anak.